Upregulation of the Adhesin Gene EPA1 Mediated by PDR1 in Candida glabrata Leads to Enhanced Host Colonization - Luis A. Vale-Silva (American Society for Microbiology, 2016)
ABSTRACT Candida glabrata is the second most common Candida species causing disseminated infection, after C. albicans. C. glabrata is intrinsically less susceptible to the widely used azole antifungal drugs and quickly develops secondary resistance. Resistance typically relies on drug efflux with transporters regulated by the transcription factor Pdr1. Gain-of-function (GOF) mutations in PDR1 lead to a hyperactive state and thus efflux transporter upregulation. Our laboratory has characterized a collection of C. glabrata clinical isolates in which azole resistance was found to correlate with increased virulence in vivo. Contributing phenotypes were the evasion of adhesion and phagocytosis by macrophages and an increased adhesion to epithelial cells. These phenotypes were found to be dependent on PDR1 GOF mutation and/or C. glabrata strain background. In the search for the molecular effectors, we found that PDR1 hyperactivity leads to overexpression of specific cell wall adhesins of C. glabrata. Further study revealed that EPA1 regulation, in particular, explained the increase in adherence to epithelial cells. Deleting EPA1 eliminates the increase in adherence in an in vitro model of interaction with epithelial cells. In a murine model of urinary tract infection, PDR1 hyperactivity conferred increased ability to colonize the bladder and kidneys in an EPA1-dependent way. In conclusion, this study establishes a relationship between PDR1 and the regulation of cell wall adhesins, an important virulence attribute of C. glabrata. Furthermore, our data show that PDR1 hyperactivity mediates increased adherence to host epithelial tissues both in vitro and in vivo through upregulation of the adhesin gene EPA1. IMPORTANCE Candida glabrata is an important fungal pathogen in human diseases and is also rapidly acquiring drug resistance. Drug resistance can be mediated by the transcriptional activator PDR1, and this results in the upregulation of multidrug transporters. Intriguingly, this resistance mechanism is associated in C. glabrata with increased virulence in animal models and also with increased adherence to specific host cell types. The C. glabrata adhesin gene EPA1 is a major contributor of virulence and adherence to host cells. Here, we show that EPA1 expression is controlled by PDR1 independently of subtelomeric silencing, a known EPA1 regulation mechanism. Thus, a relationship exists between PDR1, EPA1 expression, and adherence to host cells, which is critical for efficient virulence. Our results demonstrate that acquisition of drug resistance is beneficial for C. glabrata in fungus-host relationships. These findings further highlight the challenges of the therapeutic management of C. glabrata infections in human patients.